2006
DOI: 10.1002/cncr.22208
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma of the lung compared with other histotypes shows higher messenger RNA and protein levels for thymidylate synthase

Abstract: BACKGROUND.In patients with cancer, one of the main mechanism of resistance to antimetabolite drugs is related to higher levels of thymidylate synthase (TS) activity.METHODS.To investigate the association between TS expression and histopathologic data, 56 resection specimens from patients with nonsmall cell lung carcinoma (NSCLC) were collected consecutively. TS messenger RNA (mRNA) was evaluated in tumor specimens by using real‐time polymerase chain reaction (PCR) analysis; protein expression was evaluated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
223
5
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 349 publications
(258 citation statements)
references
References 30 publications
23
223
5
7
Order By: Relevance
“…The data from this study indicate significantly higher thymidylate synthase expression levels in squamous cell carcinomas than adenocarcinomas, consistent with prior studies (using both immunohistochemistry and direct mRNA measurement 15,25 ) regarding histology and thymidylate synthase. This study also identifies high thymidylate synthase expression in Table 3 Summary of EGFR and KRAS mutations in the adenosquamous specimens, including the microdissection cases adenosquamous tumors, showing more similarity to squamous cell specimens than adenocarcinomas.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The data from this study indicate significantly higher thymidylate synthase expression levels in squamous cell carcinomas than adenocarcinomas, consistent with prior studies (using both immunohistochemistry and direct mRNA measurement 15,25 ) regarding histology and thymidylate synthase. This study also identifies high thymidylate synthase expression in Table 3 Summary of EGFR and KRAS mutations in the adenosquamous specimens, including the microdissection cases adenosquamous tumors, showing more similarity to squamous cell specimens than adenocarcinomas.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, a recent pivotal phase III study showed improved overall survival with maintenance pemetrexed therapy following four cycles of platinum-based first-line chemotherapy in patients with advanced non-small cell lung cancer only in the non-squamous as opposed to the squamous subset. 14 Squamous cell carcinomas are known to have higher levels of thymidylate synthase expression than adenocarcinomas, 15 and it is speculated that the efficacy of pemetrexed partially depends upon the level of thymidylate synthase expression. [16][17][18] Accordingly, pemetrexed is approved solely for the treatment of patients with non-squamous tumors for whom it is viewed as a superior drug as compared with taxanes or gemcitabine based on the above data.…”
mentioning
confidence: 99%
“…The enzyme thymidylate synthase was differently expressed in adenocarcinoma and squamous-cell carcinoma and preliminary data in LCC indicate expression levels more closely related to those detected in squamous-cell carcinoma. 21 Similarly, the DNA repair gene ERCC1 was more highly expressed in squamous carcinomas than adenocarcinomas, but LCCs were not specifically analyzed, 22 although in another study expression levels of this gene were not correlated with specific histotypes. 23 Finally, in this study we demonstrated that the immunoprofile can be tentatively defined in at least part of cytological or biopsy samples obtained during the diagnostic work-up of a lung tumor mass.…”
Section: Discussionmentioning
confidence: 99%
“…Because of evidence that there might be a greater benefit of pemetrexed therapy among nonsquamous NSCLC patients than among squamous cell patients [3][4][5][6][7], a retrospective analysis of a histology effect on efficacy outcomes was performed. That analysis demonstrated that pemetrexed was more effective in patients with adenocarcinoma and large cell lung cancer than in patients with squamous cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%